2006
DOI: 10.1242/jcs.03089
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Connexin43 phosphorylated at S325, S328 and S330 in normoxic and ischemic heart

Abstract: The functional consequences of Connexin43 (Cx43) phosphorylation remain largely unexplored. Using an antibody that specifically recognizes Cx43 phosphorylated at serine residues 325, 328 and/or 330 (pS325/328/330-Cx43), we show that labeling of this form of Cx43 as well as of total Cx43 is restricted to the intercalated disk region of normal ventricular tissue. In ischemic heart, significant relocalization of total Cx43 to the lateral edges of myocytes was evident; however pS325/328/330-Cx43 remained predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
182
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(195 citation statements)
references
References 32 publications
(53 reference statements)
13
182
0
Order By: Relevance
“…2a, b). In particular, TRPC1-siRNA induced a robust decrease in the P0 and P1 forms, without substantially modifying the levels of P2 forms, which have been previously reported to correspond to Cx43 protein phosphorylated at specific serine residues (S325, S328, and/or S330) [40]. These data indicated that other GdCl 3 -sensitive channels, rather than TRPC1, specifically regulated P2 forms.…”
Section: Trpc1/ca 2? Channels Are Involved In Cx43 Expression/ Functisupporting
confidence: 65%
“…2a, b). In particular, TRPC1-siRNA induced a robust decrease in the P0 and P1 forms, without substantially modifying the levels of P2 forms, which have been previously reported to correspond to Cx43 protein phosphorylated at specific serine residues (S325, S328, and/or S330) [40]. These data indicated that other GdCl 3 -sensitive channels, rather than TRPC1, specifically regulated P2 forms.…”
Section: Trpc1/ca 2? Channels Are Involved In Cx43 Expression/ Functisupporting
confidence: 65%
“…Consistent with Musil and Goodenough (1991), the P2 isoform was insoluble after extraction of cells with Triton X-100 as indicated in the middle lane (Ab: Total, Prep: Tx Ins) of Fig 1A. When that same lane is simultaneously probed with an antibody (pS325) that is specific for Cx43 when it is phosphorylated at S325, S328 and/or S330, we found that only the P2 isoform was present (third lane, Ab:pS325, Prep:Tx Ins). We had previously shown that this phosphospecific antibody labeled the intercalated disk region of cardiomyocytes (Lampe et al, 2006) and that S325/328/330 phosphorylation was important in gap junction assembly (Cooper & Lampe, 2002). In Fig.…”
Section: Formation Of the P2 Isoformmentioning
confidence: 82%
“…Myocardial ischemia leads to Cx43 "dephosphorylation" (i.e., the loss of P1, P2, etc and gain of P0) and loss of localization from the intercalated disk, which likely contributes to contractile failure and arrhythmias (Beardslee et al, 2000;Schulz et al, 2003). We have shown that Cx43 localized to intercalated disks is phosphorylated at S325, S328 and/or S330 and that ischemia leads to loss of this phosphorylation and re-localization of the protein (Lampe et al, 2006).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations